Microbial source tracking of fecal contamination in stormwater runoff - Samendra Sherchan; Shalina Shahin; Joshua Alarcon; Hanna Brosky; Collin Potter; Ayokunle Christopher Dada (IWA Publishing, 2022)
Concerns over fecal contamination in stormwater canals have promoted the need for pollution control strategies, including the use of microbial source tracking, to identify fecal contamination in the Greater New Orleans Area. Surface water samples were collected over a 12-month period at five canal locations within Jefferson Parish, Louisiana. Quantitative polymerase chain reaction and the IDEXX method were used to assess the concentrations of coliforms, Escherichia coli (E. coli) and human fecal 183 bacteroides (HF183) in stormwater samples. A 100% positive detection rate of total coliforms and E. coli was observed across all tested sites. Despite the closeness of the five sites, when averaged across all sampling time points, Kruskal-Wallis tests indicated that E. coli was present at significantly different concentrations in these locations (χ2(5) = 19.8, p = 0.0005). HF183 was detected in 62% of the water samples collected during the stormwater sampling. Without further testing for HF183 markers, the conclusion from this study would have been that fecal contamination from an unknown source was always present at varying levels during the study period. Analysis of HF183 markers therefore adds another layer of conclusions to the results deductible from E. coli concentrations. A 100% E. coli detection rate, high E. coli concentrations coupled with low rates of HF183 detection particularly at the Esplanade, Poplar Street, and Bonnabel Boat Launch sites, the sites closest to the lake outlet, throughout the study period, indicate that fecal contamination at these stormwater canal sites comes primarily from non-human sources. However, the Metairie Road and Napoleon Avenue sites, which have the highest HF183 detection rates, on top of chronic pollution by other non-human sources, are also influenced by human fecal pollution, possibly because of human development and faulty infrastructure. This study highlights the advantages of the use of microbial source-tracking methods to complement traditional indicator bacteria. HIGHLIGHTS The study identified and traced fecal contamination in stormwater.; A positive relationship between Escherichia coli and HF183 marker.; 100% of sites tested positive for E. coli.; 62% of sites tested positive for the HF183 marker.; Chronic fecal pollution from non-human sources detected at all sites.;